Infraorbital foramen location in dry human skulls - Macedo, V. C.; Cabrini, R. R.; Faig-Leite, H. [UNESP] (My University, 2009)
The objective of this study was to determine the mean distance between the infraorbital foramen and the infraorbital margin, as well as the mean distance between the infraorbital foramen and the piriform aperture on both sides of dry human skulls, with the aim of improving the efficiency in clinical situations, such as surgery and anesthetic procedures. Two hundred ninety-five skulls were used (590 sides), located in the Frankfurt Plane through a craniostat. The measurements were collected by two distinct operators, with a dry tip compass and carried to a caliper. The general mean obtained between the infraorbital foramen and the infraorbital margin was 6.37 mm (±1.69 mm), with a mean of 6,28 mm (±1.79 mm) on the right side and 6.45 mm (±1.76 mm) on the left side. The general mean obtained between the infraorbital foramen and the piriform aperture was 17.67 mm (±1.95 mm), being 17.75 mm (±2.10 mm) on the right side and 17.60 mm (±2.04 mm) on the left side. There were statistically significant differences between the right and left distances of the infraorbital foramen and the infraorbital margin, verified by the Student's-t test. The results of this study allow a more precise location of the infraorbital foramen, particularly as regards the infraorbital margin, since this distance is of relevant importance as a repair point during surgical procedures involving this anatomical structure.
Keywords: Block infraorbital nerve; Infraorbital foramen; Infraorbital margin